K-Promoted Ni-Based Catalysts for Gas-Phase CO2 Conversion: Catalysts Design and Process Modelling Validation - Gandara-Loe, J.; Portillo, E.; Odriozola, J. A.; Reina, T. R.; Pastor-Pérez, L. (Frontiers in Chemistry, 2021)
The exponential growth of greenhouse gas emissions and their associated climate change problems have motivated the development of strategies to reduce CO2 levels via CO2 capture and conversion. Reverse water gas shift (RWGS) reaction has been targeted as a promising pathway to convert CO2 into syngas which is the primary reactive in several reactions to obtain high-value chemicals. Among the different catalysts reported for RWGS, the nickel-based catalyst has been proposed as an alternative to the expensive noble metal catalyst. However, Ni-based catalysts tend to be less active in RWGS reaction conditions due to preference to CO2 methanation reaction and to the sintering and coke formation. Due to this, the aim of this work is to study the effect of the potassium (K) in Ni/CeO2 catalyst seeking the optimal catalyst for low-temperature RWGS reaction. We synthesised Ni-based catalyst with different amounts of K:Ni ratio (0.5:10, 1:10, and 2:10) and fully characterised using different physicochemical techniques where was observed the modification on the surface characteristics as a function of the amount of K. Furthermore, it was observed an improvement in the CO selectivity at a lower temperature as a result of the K-Ni-support interactions but also a decrease on the CO2 conversion. The 1K catalyst presented the best compromise between CO2 conversion, suppression of CO2 methanation and enhancing CO selectivity. Finally, the experimental results were contrasted with the trends obtained from the thermodynamics process modelling observing that the result follows in good agreement with the modelling trends giving evidence of the promising behaviour of the designed catalysts in CO2 high-scale units.